Ringworm: The New Psora - Madsen, Ruy (Homœopathic Links, 2018)
In Sankaran's miasmatic classification, the Psora—Hahnemann's fundamental miasm—is reduced to a few drugs. The similarities between the patterns of psora and ringworm suggest that they are the same miasm. This hypothesis is confirmed by the understanding of the alternating pattern of the remedies still considered psoric.
Keywords: miasms; psora; ringworm; sycosis